Analysis of Factors Influencing Consumer Attitudes Towards Preloved Fashion in Indonesia - Putri, Fida Ayu Nurrizkia; Tangguh Dwi Pramono (Journal of Global Business and Management Review, 2025)
This research aims to determine the effect of dissatisfaction, fatigue, and perceived enjoyment on consumer attitudes regarding preloved fashion in Indonesia. This study targets those consumers who have at least some basic knowledge or have used shared fashion services. Purposive sampling was applied in this study, after which participants were chosen based on their knowledge and participation in the preloved fashion system. Data was gathered using an online survey and analyzed using SmartPLS software to perform validation, reliability, and hypothesis tests. The results indicate that dissatisfaction, fatigue, and perceived enjoyment are important contributors toward consumer attitudes regarding preloved fashion. This study aims at more sustainable fashion consumption patterns in younger emerging economies like Indonesia.